How can we associate an economic evaluation with a clinical trial? - Mariana Minatel BRAGA; Gabriela Manco MACHADO; Elizabeth Souza ROCHA; Maria Eduarda VIGANÓ; Laura Regina Antunes PONTES; Daniela Prócida RAGGIO
Abstract Economic evaluations in Dentistry have been increasing in recent years. They are a relevant contribution if an economic issue exists. Knowing if a new intervention is an efficient way of allocating available (and scarce) resources (the concept of opportunity costs), a well-designed economic evaluation may be helpful. One option is to conduct a trial-based economic analysis, which extracts a considerable board of information from a trial. This approach produces a more controlled result since many sources of variations might be reduced. On the other hand, some aspects could not be predicted directly from the trial or even extrapolated. Thus, combining model-based analysis may be an idea. In this paper, we intended to discuss important aspects to be considered by researchers in further economic evaluations. This paper will be systematically divided into sessions related to the study design as time horizon and perspective, health effects, costs, and data analysis. In the end, we expect the reader could be able to plan a trial-based economic evaluation, which should be a careful, meticulous, quite laborious and especially transparent process.